Gender Differences in Clinical, Angiographic and Procedural Profiles between Young Patients with Acute Coronary Syndrome undergoing Percutaneous Coronary Intervention - Cader, Fathima Aaysha; Rahman, Afzalur; Ullah, Mohammad; Rahman, Mohammad Arifur; Alam, Md Sarwar; Nasrin, Sahela; Momen, Abdul; Kundu, Samir Kumar; Chakraborty, Shubhra; Bala, Poppy (Cardiovascular Journal, 2018)
Background: Acute coronary syndrome (ACS) is increasingly prevalent among young patients, particularly in South Asia, where young patients are known to present with multiple risk factors and gender-based differences in angiographic profiles. This study aimed to compare gender differences in clinical, angiographic and procedural profiles between young patients with ACS undergoing percutaneous coronary intervention (PCI). Methods: This prospective observational study was done at the National Institute of Cardiovascular Diseases (NICVD) from April 2016 to March 2017. 190 young patients with ACS undergoing PCI were included. Clinical, angiographic and procedural variables were compared and statistically analyzed. Results: The mean age of young females and males was 43.8±6.9 years and 40.1±4.3 years respectively (p<<0.001). Young women had significantly more risk factors of hypertension (62.1% vs 33.7%, p<0.001) and diabetes (57.9% vs 31.6%, p<0.001) in comparison to young men. Smoking was significantly greater among young males (70.5% vs 0%, p<0.001). Young females had significantly better mean ejection fraction (EF) (48.4±9.3% vs 45.1±10.4%, p=0. 02). Left main coronary artery (3.2% vs. 1.1%, p=0.61) and left anterior descending artery (51.6% vs. 45.3%, p=0.38) were more frequently involved among young females. Young males showed angiographically more severe CAD and greater frequency of multivessel CAD with higher DVD (22.1%vs 18.9%, p=0.58) and TVD (18.9%vs 11.6%, p=0.15). Conclusion: Significantly more young women with ACS presented with hypertension and diabetes than young males. However, they had better ejection fraction and less severe angiographic profiles. Cardiovasc. j. 2018; 10(2): 113-120